Erratum - SBM ITB, Journal (Journal of Business and Management, 2013)
The Editor was asked by M.F. Zapran and A. Aliludin as co-authors for withdrawing a paper entitled â€œFeasibility study of a combined cycle power plant at PT Mitra Energi Batamâ€ published in the Journal of Business and Management, Volume 2, Number 2, 2013: 245-256. The request was made due to different bases and assumptions employed in analyzing the feasibility of the project compared to the recent conditions and the confidentiality of the data which was not supposed for the public use. The authors also personally apologized to the corresponding company and expressed their regret to any potential misinterpretation of the research results. The Editor granted this request so that the paper considered never appears in the journal.Â